2018
DOI: 10.1002/jcph.1320
|View full text |Cite|
|
Sign up to set email alerts
|

Using a Genetic Risk Score Approach to Predict Headache Response to Triptans in Migraine Without Aura

Abstract: A large meta-analysis of genome-wide association studies has recently identified a number of risk loci for migraine without aura (MwoA). In this study, we tested the hypothesis that a genetic risk score based on single-nucleotide polymorphisms (SNPs), previously reported to be associated with MwoA at genome-wide significance, may influence headache response to triptans in patients with migraine without aura. Genotyping of rs9349379, rs2078371, rs6478241, rs11172113, rs1024905, and rs6724624 was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(89 reference statements)
0
9
0
1
Order By: Relevance
“…One particular use of GRS may be in understanding drug reactions and efficacy of therapies. Studies to predict response and efficacy of treatment with triptans in migraineurs have used this approach [250, 251]. While sensitivity and specificity are still relatively low, the diagnostic value of GRS will improve with the discovery of more SNPs.…”
Section: Main Textmentioning
confidence: 99%
“…One particular use of GRS may be in understanding drug reactions and efficacy of therapies. Studies to predict response and efficacy of treatment with triptans in migraineurs have used this approach [250, 251]. While sensitivity and specificity are still relatively low, the diagnostic value of GRS will improve with the discovery of more SNPs.…”
Section: Main Textmentioning
confidence: 99%
“…Several previous studies have investigated the prediction of the outcome of migraine treatment. In patients with headache, genetic factors, migraine characteristics, and autonomic symptoms have been evaluated to predict treatment response to triptan and topiramate (26)(27)(28). In addition, white matter hyperintensity was found to predict migraine prognosis (29); however, the correlation and regression analysis between predictors and patient outcomes used in this previous study were insufficient.…”
Section: Discussionmentioning
confidence: 82%
“…Based on our lack of reproducibility and the inconclusive results from migraine, it is suggested that the rs2651899 is not a relevant predictor of triptan response. An Italian study [25] hypothesized that SNPs associated with migraine could influence triptan response and they found that rs6724624 and rs1024905 were inversely associated with inconsistent response to triptans. These findings were not replicated in our CH cohort, but the two SNPs have not been found to be associated with CH [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, one SNP (rs5443) was associated with treatment response in CH [22] and four SNPs (rs6275, rs2651899, rs1024905 TA B L E 1 Background information on the study participants. and rs6724624) with triptan response in migraine [5,[23][24][25] (Table 4). Amongst the 395 CH patients who had tried triptans, 73.4% (n = 290) were classified as triptan responders.…”
Section: Replication Of Treatment Response With Previously Reported Snpsmentioning
confidence: 99%